Successful treatment of an acute infective endocarditis secondary to fish bone penetrating into left atrium caused by Granulicatella adiacens and Candida albicans: A case report. Issue 51 (December 2017) - Tong, Ya Ling; Qu, Ting Ting; Xu, Jia; Chen, Nai Yun; Yang, Mei Fang
Abstract: Rational: Infective endocarditis caused by a foreign body of the upper digestive tract is rare. We report a rare case of Granulicatella adiacens and Candida albicans coinfection acute endocarditis combined with systematic embolization caused by a fish bone from the esophagus penetrating into the left atrium. Patient concern: A 42-year-old woman was admitted to our hospital because of fever, abdominal pain, headache, and right limb weakness. Diagnoses: Clinical examination indicated endocarditis and systemic embolisms secondary to a fish bone from the esophagus penetrating into the left atrium. The emergency surgery confirmed the diagnosis. Cultures of blood and vegetation show G adiacens and C albicans . Interventions: Antimicrobial therapy lasted 6 weeks after surgery. Outcomes: The patient was discharged with excellent condition7 weeks after hospitalization and was well when followed 6 months later. Lessons: The successful treatment of this patient combines quick diagnosis, timely surgery, and effective antimicrobial regimen. This rare possibility should be kept up in mind in acute infective endocarditis cases.